2015
DOI: 10.1038/srep13958
|View full text |Cite
|
Sign up to set email alerts
|

In silico modeling of spore inhalation reveals fungal persistence following low dose exposure

Abstract: The human lung is constantly exposed to spores of the environmental mould Aspergillus fumigatus, a major opportunistic pathogen. The spectrum of resultant disease is the outcome of complex host-pathogen interactions, an integrated, quantitative understanding of which lies beyond the ethical and technical reach permitted by animal studies. Here we construct a mathematical model of spore inhalation and clearance by concerted actions of macrophages and neutrophils, and use it to derive a mechanistic understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…For example, persistence of live A. fumigatus conidia for more than several days in both mouse (Tanaka et al, 2015) and zebrafish (Knox et al, 2014) models supports the efficacy of fungal spore defences (Aimanianda et al, 2009; Akoumianaki et al, 2016) conferring a tolerance to host inflicted stress. Furthermore, as a certain percentage of spores persist in vivo it is still unclear the spatial and temporal factors surrounding fungal killing.…”
Section: Discussionmentioning
confidence: 91%
“…For example, persistence of live A. fumigatus conidia for more than several days in both mouse (Tanaka et al, 2015) and zebrafish (Knox et al, 2014) models supports the efficacy of fungal spore defences (Aimanianda et al, 2009; Akoumianaki et al, 2016) conferring a tolerance to host inflicted stress. Furthermore, as a certain percentage of spores persist in vivo it is still unclear the spatial and temporal factors surrounding fungal killing.…”
Section: Discussionmentioning
confidence: 91%
“…Several, currently insurmountable, technical challenges might be usefully circumvented by the use of computational approaches. For example, in support of a protective role for AEC-mediated activities, agent-based modelling of the human alveolus predicts that chemotactic signalling by AECs is required for the efficient recruitment of alveolar macrophages during early A. fumigatus infection [ 85 ] and low-dose exposure to A. fumigatus spores prompts fungal persistence in both in silico and murine models of pulmonary aspergillosis [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompetent hosts, neutrophils form complexes with conidia that possess NADPH oxidase activity, thereby inhibiting germination [118]. Using in silico modeling, a recent report demonstrated that 6–17 hours after initial exposure, neutrophil- rather than macrophage-mediated killing of Aspergillus is the dominant conidiacidal response[119]. In addition, iron sequestration by lactoferrin secreted in neutrophilic granules is involved in restricting the initial germination of conidia [120, 121].…”
Section: Myeloid Responsesmentioning
confidence: 99%